Expert Evidence - Gross, Samuel R. (1991)
It seems that the use of expert witnesses in common law courts has always been troublesome. In his Treatise on the Law of Evidence, first published in 1848, Judge John Pitt Taylor describes several classes of witnesses whose testimony should be viewed with caution, including: enslaved people (which accounts for the lamentable neglect of truth, which is evinced by most of the nations of India, by the subjects of the Czar, and by many of the peasantry in Ireland ); women (because they are more susceptible to an innate vain love of the marvelous ); and foreigners and others ... living out of the jurisdiction (who have little fear of the consequences of perjury). But, [p]erhaps the testimony which least deserves credit with a jury is that of skilled witnesses .... [Ilt is often quite surprising to see with what facility, and to what extent, their views can be made to correspond with the wishes and interests of the parties who call them. 1 While others of Judge Taylor's stereotypes have not stood the test of time, this last one has been remarkably durable. It was no novelty in 1848, and with a little effort one can find an abundance of similar comments from lawyers and judges in every decade since.2 In fact, we have become thoroughly accustomed to this view of experts. And yet isn't it remarkable-isn't it, in fact, shocking-that casual observers and even interested partisans are treated by the legal profession with at least reasonable respect, but trained and experienced doctors, engineers and scientists are castigated